CONTRACEPTION AND FEMININITIES: AN ANALYSIS OF THE RESISTANCE TO THE PILL - Cuevas Barberousse, Tania (2014)
This article analyses why a group of women abandoned the contraceptive pill. It arguesthat this decision can be analyzed as a form of resistance to certain representations,values, and practices inscribed in the pill. In this case, the contraceptive pill is consideredas a gender script. The study of the experiences of a group of women reveals that, undercertain conditions, the notion of the contraceptive pill as an intrinsically emancipatorytechnology can be challenged.